Effects of shear temperature-controlled entanglement network on the structure evolution of Poly(ethylene oxide) in shear flow. (8th May 2019) - Li, Kun; Matsuba, Go
Abstract: This study investigated the structure evolution of poly (ethylene oxide) (PEO) samples sheared at different temperatures above the equilibrium melting temperature followed by cooling to an isothermal temperature of 50 °C. We found that the higher shear temperature tended to decrease the number of entanglements to generate a larger network deformation, which was characterized by the deviation angle. It improved the orientation of chains and noticeably accelerated the crystallization process, however the final values of the long period, lamellae thickness and amorphous thickness remained almost similar. Based on the statistical theory of rubber elasticity, we proved that numerous entanglements, which were characterized by the longest relaxation time or the zero shear viscosity, indeed prevented the extension of chains when the concentration of the long chains was much higher than the long chain overlap concentration. Graphical abstract: PEO structure evolution induced by the shear temperature-controlled entanglement network deformation.Image 100118 Highlights: Shear temperature above T m 0 influenced the PEO structure evolution at the same isothermal crystallization temperature. Higher shear temperature preferred a larger network deformation characterized by deviation angle. The entropy of shear temperature controlled-entanglement network depended on the number of entanglements.